Leadership Character Education Strategy on Darussalam Gontor Ponorogo Student Organization Management (OPPM) - Rifaie, Muhammad Mukrim Faer; Khoir, Abdul; Alkhotob, Imam Taufik (Proceeding International Conference on Education, 2023)
Leadership character education in an educational institution is necessary to produce better Human Resources (HR). This study aims to analyze the concept of leadership character education and analyze strategies for implementing leadership character education for OPPM administrators at Pondok Modern Darussalam Gontor Ponorogo. Data collection techniques include interviews, observation, and documentation. This study uses the interactive analysis model of Miles and Huberman. The results showed that the leading character education strategy applied to OPPM Darussalam Gontor management positively impacted the formation of leadership character. Through self-development activities, leadership training, fostering ethical values, and participation in the organization, OPPM officials can develop leadership skills, honesty, integrity, responsibility, and teamwork. This research implies the importance of continuing and developing leadership character education strategies for OPPM administrators and other student organizations. It will contribute to producing young people who have strong leadership skills and are responsible for building a better society.